Sensilla Trichoidea-Inspired, High-Temperature, and Omnidirectional Vibration Perception Based on Monolayer Graphene - Li, Yuning; Chen, Danke; Tang, Xiaoqiu; Yu, Peizhi; Sun, Jingye; Li, Xue; You, Qing; Zhu, Mingqiang; Gao, Chang; Li, Linan; Tian, He; Deng, Tao (Nano-Micro Letters, 2026)
With the convergence of sensor technology, artificial intelligence, and the Internet of Things, intelligent vibration monitoring systems are undergoing transformative development. This evolution imposes stringent demands on the miniaturization, low power consumption, high integration, and environmental adaptability of transducers. Graphene, renowned for its superlative physicochemical attributes, holds significant promise for application in micro- and nanoelectromechanical systems (M/NEMS). However, the inherent central symmetry of graphene restricts its utility in piezoelectric devices. Inspired by the sensilla trichoidea of spiders, a three-dimensional (3D) cilia-like monolayer graphene omnidirectional vibration transducer (CGVT) based on a stress-induced self-assembly mechanism is fabricated, demonstrating notable performance and high-temperature resistance. Furthermore, 3D vibration vector decoding is realized via an omnidirectional decoupling algorithm based on one-dimensional convolutional neural networks (1DCNN) to achieve precise discrimination of vibration directions. The 3D bionic vibration-sensing system incorporates a spider web structure into a bionic cilia MEMS chip through a gold wire bonding process, enabling the realization of three distinct mechanisms for vibration detection and recognition. In particular, these devices are manufactured using silicon-based semiconductor processing techniques and MEMS fabrication methodologies, leading to a substantial reduction in the dimensions of individual components compared to traditional counterparts. Highlights: 1 Bioinspired MEMS vibration perception: The monolithic integration of three-dimensional semicircular biomimetic ‘cilia’-structured vibration transducer arrays based on monolayer graphene was achieved by a controlled stress-driven self-assembly technique. 2 High Performance: The 3D vibration transducer array enables real-time, high-performance (87.95 pC g−1), and wide-range vibration monitoring (1 Hz–10 kHz, 0–1120 g) under dynamic loading, while achieving omnidirectional vibration signal acquisition and decoupling. 3 Resistant to high temperatures: Stable vibration responses at ultrahigh temperatures up to 800 °C are achieved with merely a 20-nm-thick Si3N4 protective coating.